Review: Saffron’s Activity as an Active Ingredient in Cosmetics - Irna Roniawati; Norisca Aliza Putriana; Adinda Naswa Putri; Yuniar Alfain Nur’aini (Universitas Padjadjaran (Unpad), 2021)
Saffron (Crocus sativus) is a plant that has been widely used in Asia, especially in the health sector. This can be related to other than that saffron is also known for its use as a cosmetic because Saffron has various kinds of pharmacological activities beneficial to human skin. Today's cosmetic users prefer cosmetics with herbal or natural ingredients, especially in Indonesia. This happens because it is considered that herbal cosmetics are safer and harmless in long-term use. Therefore, it is necessary to do related act ivities of saffron as a cosmetic ingredient. This is narrative research where the data is obtained from PubMed, Science Direct, and Google Scholar with keywords Saffron, Saffron for cosmetics, and others. There were eight references, with inclusion criteria being national and international journals and national websites published in 2011-2021, especially regarding the study of saffron activity as an ingredient for cosmetics. Then the data is analyzed narratively. It was found that Saffron (Crocus sativus) contains compounds that have a cosmetic activity such as safranal which can be used as a perfume, crocin as an antioxidant and as anti-dark spot, crocin, safranal, and crocetin as anti-UV, crocin, and crocetin as an anti-inflammatory and as coloring pigment in cosmetics, vitamin C, flavonoids and zinc as a face toner, kaempferol, crocin and crocetin as anti-wrinkle, zeaxanthin, lycopene, carotene, crocetin, picrocrocin, kaempferol, and crocin as anti-aging. Saffron (Crocus sativus) has various beneficial activities for the skin, so it can be used as an ingredient in making cosmetics.Keywords : Cosmetics, Herbal, Saffron, Herbal Cosmetics, Active Ingredient